Moving Communities: Climate change and the possibilities of protected land - Brabec, Elizabeth (SelectedWorks, 2022)
The distant prospect of moving communities due to climate change is here – in the United Statesand around the world. For villages such as Newtok in Alaska and Ile de Jean Charles in Louisiana,sea level rise and increasing storm events has made the communities unlivable: salinization ofwells, melting of permafrost, shoreline erosion and the repeated storm damage has made theoption to move the only choice (Kay 2019; Galik and Smith 2020).However, the movement of whole communities requires sufficient land area to support therelocation of tens to hundreds of households. It is not only the households that must be moved,but people’s livelihoods, community social structure, and in many cases a shared sense ofheritage.Currently, a number of the communities in the United States who are in the active process ofmoving are relocating to government-owned or protected lands. Internationally, National Parksin African countries such as Kenya and Tanzania have served for years as temporary or evensemi-permanent camps that can house refugees fleeing war and famine (Odenigbo 2016). Thisis likely to become a reality for community displacement and relocation facing both the developedand developing worlds.Given the scope of the movement of communities out of the way of flooding, extreme stormevents, wildfires and drought, planners need to consider the available lands that couldaccommodate these communities. Protected lands and open space as a national resourceprovide opportunities and constraints for displaced communities. This paper reviews the legalconstraints in the United States to the use of protected open space for communityrelocation. Whether government owned or held under perpetual easements by community landtrusts or other NGOs, community open space may provide the best – or only - options forcommunity relocation.